Our Present Experience with Treatment of Children and Adolescents in Conscious Sedation Using N₂O/O₂ - L. Navarová; J. Handzel (Czech Dental Chamber, 2008)
From November 2004 to October 2007 we realized 131 dental treatments in conscious sedation by nitrous oxide/oxygen in a group of 57 boys and 37 girls aged 4-17 years. There were 79 treatments in boys and 52 in girls, 28 children underwent the sedation repeatedly. The indications were mainly the dental fear, in a smaller part of the group the psychological immaturity for the planned procedure. The treatment consisted mostly in teeth extractions, restorative procedures, and mucogingival surgery. This form of conscious sedation represents an appropriate choice of treatment of anxious children in school age and in adolescence.